Household air pollution exposure in sub-Saharan Africa and assessment of disease burden attributable to risk factor - Balidemaj,Festina (2020)
BACKGROUND: One of the major environmental threats to human health is air pollution. It contributes to premature deaths of millions of people worldwide. Air quality issues are growing exponentially in developing countries (West et al. 2016). More specifically, household air pollution that results from indoor cooking with solid fuels is damaging to the human health in LMIC. About 54% of global population in low and middle income countries (LMIC) relies on polluting fuel (including wood and dung) for cooking (WHO, 2016). Very high emissions of particulate matter (PM), short-lived climate forcers and polycyclic aromatic hydrocarbons (PAHs) result from inefficient combustion of solid fuel in household stoves (Ramanathan, 2008). While outdoor and household air pollution can be detrimental to everyone, a subpopulation particularly at risk is that including pregnant women. METHODS: 2114 pregnant women were surveyed regarding their cooking habits and fuel-type use for cooking purposes in Adama of Ethiopia, Africa; an area of 600 000 inhabitants. AirQ+ software was used to assess health impact of household air pollution through estimating disease burden (including Acute Lower Respiratory Infections, Chronic Obstructive Pulmonary Disease, Ischemic Heart Disease, Lung Cancer, and Stroke) attributable to risk factor. RESULTS: Fifty-nine per cent of the cohort group of Adama, Ethiopia, use solid fuel (such as coal) for cooking purposes. As a result, the BoD estimation of mortality rate per 100 000 Adama women, using age-standardized mortality rates of women of Ethiopia is 33 for ALRI, 9 for COPD, 23 for IHD, 12 for LC, and 11 for stroke. Burden of Disease DALYs estimation per 100 000 women of Adama is using DALYs per 100 000 Ethiopian women of ages 15-49 is 4,265 DALYs for ALRI, 629 DALYs for COPD, 1,123 DALYs for IHD, 53 DALYs for LC, and 753 DALYs for stroke. While 95.2% of Adama population have electricity at home, 42.8% use if for cooking, the rest using solid fuel or a combination of electricity and solid fuel. Other factors, such as education level, location of cooking, and presence of running water at home have shown to impact fuel-type use in the cohort population. CONCLUSION: This health impact assessment leads to the knowledge that household air pollution due to solid fuel use (such as charcoal) among pregnant women in Adama, Africa, leads to mortality rates and disease-adjusted life years that could be avoided by decreasing or eliminating solid fuel use for cooking purposes.
Keywords: Air pollution; household air pollution; burden of disease; acute lower respiratory infection; chronic obstructive pulmonary disease; ischemic heart disease; lung cancer; stroke; sub-Saharan Africa